2018
DOI: 10.1515/icame-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating stance-annotated sentences from the Brexit Blog Corpus: A quantitative linguistic analysis

Abstract: This paper offers a formally driven quantitative analysis of stance-annotated sentences in the Brexit Blog Corpus (BBC). Our goal is to identify features that determine the formal profiles of six stance categories (contrariety, hypotheticality, necessity, prediction, source of knowledgeanduncertainty) in a subset of the BBC. The study has two parts: firstly, it examines a large number of formal linguistic features, such as punctuation, words and grammatical categories that occur in the sentences in order to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…As a second step, we calculated the pair-wise combinations of the stance categories. Confirming our quantitative study [33], the contrariety and necessity binary classification achieved the best results with up to 71% accuracy. This result was encouraging and highlighted the fact that each stance category has a different level of distinctness, with contrariety and necessity as the most discriminative ones.…”
Section: Background Worksupporting
confidence: 80%
See 2 more Smart Citations
“…As a second step, we calculated the pair-wise combinations of the stance categories. Confirming our quantitative study [33], the contrariety and necessity binary classification achieved the best results with up to 71% accuracy. This result was encouraging and highlighted the fact that each stance category has a different level of distinctness, with contrariety and necessity as the most discriminative ones.…”
Section: Background Worksupporting
confidence: 80%
“…We compiled a manually annotated corpus according to this framework, and performed various qualitative, quantitative and computational tasks in order to identify patterns in language that are associated to each stance. We highlighted six out of ten stance categories as the most frequent ones in our corpus: contrariety, hypotheticality, necessity, prediction, source of knowledge and uncertainty, and showed that stances such as contrariety and necessity, are more distinctive than other [33]. In this paper, we applied the corpus-, quantitative-, and computational-based features that were highlighted as important in our previous studies in a data set extracted from social media.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Its discourse characteristics are widely discussed (e.g. [Simaki et al 2018]; [Berger, Hennig 2015]; [Germasheva 2010] etc.). It is generally assumed that it combines properties of written and spoken modes and, besides, manifests its own features.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we investigate multilabel stance detection in the context of three datasets: the Brexit Blog Corpus (BBC) (Simaki et al, 2018), the US Election Tweets Corpus (ETC) (Sobhani et al, 2019), and the Moral Foundations Twitter Corpus (MFTC) (Dehghani et al, 2019). Figure 1 shows examples from each dataset where the utterances have been annotated with multiple stances.…”
Section: Introductionmentioning
confidence: 99%